Zinc(II) and cadmium(II) binary complexes with creatinine and their mixed-ligand complexes with L-asparagine or L-glutamic acid: Potentiometric studies - (:unkn) unknown (FREUND PUBLISHING HOUSE LTD, 2006)
Creatinine is a physiological component of blood, brain and muscles and an important bioligand, which is the last product of the nitrogen metabolism in the vertebrates. In this study, the stability constants of binary complexes formed by creatinine with Zn(II) and Cd(II), and of the mixed-ligand complexes Zn(II)-creatinine-1-asparagine and Zn(II) creatinine-l-glutamic acid were determined by the Calvin-Bjerrum and Irving-Rossotti methods. The conditional formation constants and the formation pH ranges of complexes were determined. Relative abundance was plotted using conditional formation constants of the complexes and the steps of the complexes are shown in graphs. The composition of metal-creatinine complexes was determined as metal/ligand = 1: 1.
Keywords: stability constant; creatinine; l-asparagine; l-glutamic acid; zinc; cadmium; complex; ligand; MOLECULAR-STRUCTURE; CRYSTAL